The International Meeting on Chemical Sensors: Serving the Chemical Sensing Community for More Than Three Decades. (1st January 2019) - Semancik, Steve; Shimizu, Yashuro; Lieberzeit, Peter
Abstract : The acronym IMCS stands for the well-known "International Meeting on Chemical Sensors" conference series that convenes every two years. Having started in 1983 in Fukuoka, Japan, it is now one of the largest forums worldwide in the field of chemical sensing. IMCS2020 will be co-hosted with the 237th ECS Spring Meeting in Montreal, Canada. This paper introduces the IMCS conference series to the audience of the ECS.